Collaboration to data curation : harnessing institutional expertise - Macdonald, S; Martinez-Uribe, L (Routledge, 2010)
It can be argued that institutional repositories have not had the impact (Lynch 2003, Salo 2008), initially expected, on academic scholarly communications (the exception being in a few well-developed and successful instances). So why should data repositories expect to fare any better? Firstly, data repositories can learn from publication repositories experiences and their efforts to engage researchers to accept and use these new institutional services. Secondly, they provide a technical infrastructure for storing and sharing data with the potential for providing access to complimentary research support facilities. Finally, due to the interdisciplinary expertise required to develop and maintain such systems, stronger ties will be forged between libraries, information and computing services, and researchers which will assist innovation and help to make them sustainable and embedded within academic institutional policy. This paper, whilst aware of the diverse nature of institutional and departmental practices, aims to highlight a number of initiatives that will show how research data repository infrastructures can be effectively realised through collaboration and sharing of expertise. We argue that by employing agile community, strategic and policy judgment a robust data repository infrastructure will be part of an integrated solution to effectively manage institutional research data assets.